EFFECT OF EXERCISE ON THE LEVEL OF IMMUNOGLOBULIN A IN SALIVA - Teresa Trochimiak; Elżbieta Hübner-Woźniak (Termedia Publishing House, 2012)
The aim of this paper is to describe the structure, production and function of secretory immunoglobulin A (sIgA) as well as changes of its concentration caused by exercise of various intensity and duration. Immunoglobulin A is the main class of antibodies present in the body secreted fluids such as saliva, tears or mucus from the intestines. It is generally recognized that IgA, due to its dominance in the immune system of mucous membranes, is the first line of defence against harmful environmental factors. The secretion and composition of saliva depends on the activity of the sympathetic and parasympathetic nervous systems. Physical activity, stimulating the autonomous nervous system, may reduce the amount of saliva and/or inhibit its secretion. The relationship between physical activity and the suppression of the immune system is not fully understood, but it is known that moderate intensity exercise can improve immune defences, while extreme effort can reduce them by creating an increased risk of upper respiratory tract inflammation (URTI). In athletes, the lowest risk of upper tract infection was connected with the case of moderate intensity exercise. It is now believed that the relationship between exercise volume and the risk of URTI has the shape of the letter "J". This means that both too little and too much physical activity may increase the risk of upper respiratory tract infection. Training optimization and correct balance between exercise and rest periods may reduce the risk of adverse changes in the immune system and decrease the frequency of URTI.